2021
DOI: 10.1111/jcmm.16954
|View full text |Cite
|
Sign up to set email alerts
|

Aucubin prevents steroid‐induced osteoblast apoptosis by enhancing autophagy via AMPK activation

Abstract: Steroid-induced osteoblast apoptosis is a crucial pathological process in steroidinduced osteonecrosis of the femoral head (SONFH). Autophagy can resist apoptosis and AMPK plays an important role in autophagy regulation. Aucubin from the small tree Eucommia ulmoides Oliv., which has a long history of use in orthopaedics and traumatology in Asian medicine, can promote bone formation, but whether it can slow or prevent steroid-osteoblast apoptosis is unclear. Therefore, we investigated the pathogenesis of SONFH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Autophagy has many physiological and pathophysiological roles in a variety of diseases ( Mizushima, 2007 ). For example, increasing autophagy can reduce steroid-induced apoptosis of bone cells ( Yue et al, 2021 ) and protect cells from premature aging ( Rossiter et al, 2021 ). In addition, activation of FUNDC1-dependent mitophagy protects neurons against cerebral I/R injury ( Cai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy has many physiological and pathophysiological roles in a variety of diseases ( Mizushima, 2007 ). For example, increasing autophagy can reduce steroid-induced apoptosis of bone cells ( Yue et al, 2021 ) and protect cells from premature aging ( Rossiter et al, 2021 ). In addition, activation of FUNDC1-dependent mitophagy protects neurons against cerebral I/R injury ( Cai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Network analysis showed that aucubin, geniposide, reptoside and ajugoside were the core compounds of IGEUs against OP. Aucubin had strong anti-OP activity, which can not only increased the differentiation of osteoblasts, promote the increase of cortical bone thickness and bone density, but also prevented the apoptosis of osteoclasts 71 , 72 . Moreover, we have also reported that the total glycosides in Eucommia ulmoides seeds contain high content of aucubin, which could enhance bone mineral density and bone strength, suggesting that it may be a potential alternative drug for the treatment of OP 73 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aucubin prevents apoptosis in osteoblasts via the AMPK-regulated autophagy pathway. 39 Therefore, we selected autophagy as a downstream signalling pathway of AMPK to resolve palmitate-induced apoptosis in tenocytes. DEL-1 treatment upregulates autophagy markers and autophagosome biogenesis.…”
Section: Discussionmentioning
confidence: 99%